2015
DOI: 10.4103/0253-7613.150377
|View full text |Cite
|
Sign up to set email alerts
|

Reversible bilateral ototoxicity in a patient with chronic hepatitis B during peginterferon alpha-2a treatment

Abstract: Peginterferon alpha-2a (PEG IFN α-2a) is frequently used in chronic hepatitis B (CHB)treatment. Numerous adverse events can be noted during this therapy such as flu-like disease, rash, weight loss and depression. However, PEG IFN α-2a related ototoxicity seems to be an uncommon entity. Ototoxicity can be detected objectively by audiometry. In this paper, we present a case of CHB who developed reversible bilateral ototoxicity during PEG IFN α-2a treatment. Due to ototoxicity detected objectively by audiogram, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Third, a population-based study cannot clarify the real mechanism underlying the association between HBV/HCV infection and SSNHL because extracting cochlear tissue pathogens or detecting cochlear injury through imaging is very difficult [7, 8]. In addition, patients who developed SSNHL due an ototoxic effect after antiviral drug administration for HVB/HCV infection (which has been reported in some studies) could not be excluded [10, 11]. However, a case–control study revealed pegylated interferon plus ribavirin therapy does not have any impact on the hearing thresholds of patients with HCV [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, a population-based study cannot clarify the real mechanism underlying the association between HBV/HCV infection and SSNHL because extracting cochlear tissue pathogens or detecting cochlear injury through imaging is very difficult [7, 8]. In addition, patients who developed SSNHL due an ototoxic effect after antiviral drug administration for HVB/HCV infection (which has been reported in some studies) could not be excluded [10, 11]. However, a case–control study revealed pegylated interferon plus ribavirin therapy does not have any impact on the hearing thresholds of patients with HCV [29].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis virus infection has been correlated with SSNHL in only a small number of case reports [811]. Hepatitis B virus (HBV) and hepatitis C virus (HCV) infections have emerged as a global health problem, and as many as 350 million and 123 million individuals have been infected with HBV and HCV, respectively, worldwide [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…There is limited data on the ototoxic effects of ribavirin, and it is possible that IFN/ribavirin ototoxicity is due to non-pegylated IFNs alone rather than ribavirin. However, hearing loss caused by IFN therapy is usually reversible ( 61 ), whereas (PEG)-IFN/ribavirin therapy can cause permanent hearing loss ( 62 ), suggesting that ribavirin itself may be ototoxic, with a potentiating or synergistic effect where co-treatment with ribavirin exacerbates IFN ototoxicity.…”
Section: Candidate Covid-19 Pharmacotherapeutics With Known Ototoxicitymentioning
confidence: 99%
“…Recent clinical trials showed that IFN-α therapy significantly reduced viral shedding and levels of inflammatory biomarkers, whereas IFN-β therapy improved virologic clearance; both therapies led to improved recovery in patients with COVID-19 ( 68 , 69 ). Clinical studies have shown reversible hearing loss in patients receiving either IFN-α or IFN-β therapy ( 61 , 70 ) via an unknown mechanism, while co-treatment with IFN and other therapies, such as ribavirin can lead to permanent hearing loss ( 62 ). Elevated ABR thresholds were observed in albino Swiss mice after treatment with IFN-α2A, likely due to fibroblast cell toxicity in the spiral limbus ( 71 ).…”
Section: Candidate Covid-19 Pharmacotherapeutics With Known Ototoxicitymentioning
confidence: 99%